(3cJGH aj JGQjN GdeZQH hHYV HjhJ aGSs
(3ChdgG (B:s
(3Chdg eHJhQ , hChd GdehLhO efg(B: (3GHf Gdedc SHC Hf Gdedc jTLH , HSchf GdTjf GdeYLeI hVe GdHGA , Hf Gdedc jYQH Hf Gdedc bMWGf PcQ HYV eTGgjQ CYjGf aGS s
(3BNQgG (B:s
(3hBNQg eHJhQ CjVkG hBNQ JQLeI ebQhAI ajg JQLeI CHj YHOGddg eMeO Hf Gdabjg CHj HcQ GdMejOj GdaGSj GdeJhaj SfI NeS hSHYjf hKeGfeGFI hjfJgi GdcJGH GdYHGQI Gdabjg GdNWjH GdMGL CHhjMji CHhHcQ s
(3Vef eLehY , JQJjHgG (B: (3ef U H (B17 - (3U C (B34s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B338 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs